Influence of ossicular chain malformation on the performance of round-window stimulation: A finite element approach. (May 2019) - Liu, Houguang; Zhang, Hu; Yang, Jianhua; Huang, Xinsheng; Liu, Wen; Xue, Lin
As a novel application of implantable middle ear hearing device, round-window stimulation is widely used to treat hearing loss with middle ear disease, such as ossicular chain malformation. To evaluate the influence of ossicular chain malformations on the efficiency of the round-window stimulation, a human ear finite element model, which incorporates cochlear asymmetric structure, was constructed. Five groups of comparison with experimental data confirmed the model's validity. Based on this model, we investigated the influence of three categories of ossicular chain malformations, that is, incudostapedial disconnection, incus and malleus fixation, and fixation of the stapes. These malformations' effects were evaluated by comparing the equivalent sound pressures derived from the basilar membrane displacement. Results show that the studied ossicular chain malformations mainly affected the round-window simulation's performance at low frequencies. In contrast to the fixation of the ossicles, which mainly deteriorates round-window simulation's low-frequency performance, incudostapedial disconnection increases this performance, especially in the absence of incus process and stapes superstructure. Among the studied ossicular chain malformations, the stapes fixation has a much more severe impact on the round-window stimulation's efficiency. Thus, the influence of the patients' ossicular chain malformations should be considered in the design of the round-window stimulation's actuator. The low-frequency output of the round-window simulation's actuator should be enhanced, especially for treating the patients with stapes fixation.